From Mechanisms to Treatment: A Comprehensive View of Lymphatic Metastasis in Cancer - Nitya Devisetti; Pushti Shah; Farrah C. Liu (Lymphatics)
The lymphatic system, a complex and dynamic network comprising lymphatic vessels, lymph nodes (LNs), and associated lymphoid tissues, plays a pivotal role in regulating interstitial fluid balance and providing immune surveillance across the body. In cancer, however, the lymphatic system often transforms into a pathway for malignant cell dissemination, leading to lymphatic metastasis—a significant step in tumor progression associated with worse patient prognoses. Mechanistically, tumor cells exploit lymphangiogenic pathways to facilitate their entry and spread within the lymphatic network. Key mechanisms in this process include the upregulation of vascular endothelial growth factors C and D (VEGF-C/D), which promote lymphatic endothelial proliferation, vessel dilation, and increased permeability. This review seeks to provide an in-depth examination of the biological mechanisms underpinning lymphatic metastasis, explore its impact on cancer progression, and highlight current and emerging strategies aimed at managing metastatic disease.